2007
DOI: 10.1136/bjo.2007.118661
|View full text |Cite
|
Sign up to set email alerts
|

Expression of apoptosis-related markers in malignant epithelial tumours of the lacrimal gland and their relation to clinical outcome

Abstract: The correlation with survival of apoptotic index, p53 and Bcl-2 expression suggest the more tumour cells go in apoptosis, upregulating p53 and down-regulating Bcl-2, the better the survival of patients. This study establishes a role of apoptosis-regulatory proteins in the pathogenesis of malignant epithelial lacrimal gland tumours, and supports the hypothesis that evaluation of the expression of apoptosis-related markers in these tumours may provide a prognostic tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…When mutated, p53 fails in leading all the damaged cells to apoptosis and some progress then further to full-blown cancer. A similar correlation between the levels of p53 and TUNEL was recently reported by strianese et al 16 who examined lachrymal gland malignancies. The fact that we found no significant correlation between the expression rates of Skp2 and heparanase, despite the fact that both were associated with poor survival, may be explained by their being involved in unrelated lethal pathways.…”
Section: Methodssupporting
confidence: 56%
“…When mutated, p53 fails in leading all the damaged cells to apoptosis and some progress then further to full-blown cancer. A similar correlation between the levels of p53 and TUNEL was recently reported by strianese et al 16 who examined lachrymal gland malignancies. The fact that we found no significant correlation between the expression rates of Skp2 and heparanase, despite the fact that both were associated with poor survival, may be explained by their being involved in unrelated lethal pathways.…”
Section: Methodssupporting
confidence: 56%
“…In contrast with these findings, Friedrich and Bleckmann showed that only the stage of the tumor had an impact on prognosis whereas the localization or the histological subtypes did not show any impact on survival [17]. Strianese et al [18 ] studied the relationship among apoptosis related markers and prognosis in 21 malignant epithelial tumors of the lacrimal gland, including 11 adenoid cystic carcinomas. They found that increased Bcl-2 staining was significantly correlated with a poor survival.…”
Section: Malignant Lacrimal Gland Tumorsmentioning
confidence: 92%
“…Differential expression of apoptotic molecules has also been seen between highly metastatic ACC cell lines compared with their less metastatic counterparts 48. The specific role of B-cell leukaemia/lymphoma 2 (BCL-2) is less clear as upregulation of BCL-2 was found to correlate with poor outcome in one study63 but not in another 64…”
Section: Metastatic Acc Of the Lacrimal Glandmentioning
confidence: 99%